Silk fibroin separators: A step toward lithium-ion batteries with enhanced sustainability - Pereira, R. F. P. (2018)
Battery separators based on silk fibroin (SF) have been prepared aiming at improving the environmental issues of lithium-ioh, batteries. SF materials with three different morphologies were produced: membrane films (SF-F), sponges prepared by lyophilization (SF-L) and: electrospuri membranes (SF-E). The latter Materials presented a suitable porons,three-dimensional microstructure and were soaked with a I M LiPF6 electrolyte: The ionic conductivities for SF-L and SF-E were 1.00 and 0.32 mS cm(-1) at 20 degrees C, respectively. A correlation between the fraction "of beta-sheet conformations and the ionic conductivity was observed. The electrochemical performance of the SF-based materials was evaluated by incorporating them in cathodic half-cells with C-LiFePO4. The discharge capacities of SF-L and SF-E were 126 and 108 mA h g(-1), respectively, at the C/Iirate and 99 and 54 mA h g(-1), respectively, at the 2C-rate. Furthermore, the capacity retention and capacity fade of the SF-L membrane after 50 cycles at the 2C-rate were 72 and 5%, respectively. These electrochemical results show that a high percentage of beta-sheet conformations, were of prime importance to guarantee excellent cycling performance. This work demonstrates that SP-based membranes are appropriate separators for the production of environmentally friendlier lithium-ion batteries.